(untitled) (Моделювання, керування та інформаційні технології, 2025)
This paper explains why adding Language Server Protocol support to an existing integrated development environment requires replacing its synchronous language support API with an asynchronous one. We explore the possibility of reusing language support code of other applications during the transition to the asynchronous API. And finally, we envision substantial additional benefits of such a transition.